PENGARUH AUDIT OPERASIONAL DALAM MENINGKATKAN EFISIENSI DAN EFEKTIFITAS TERHADAP KINERJA PEMBELIAN PADA PT ENVIROLAB NUSANTARA - Budi Tri Rahardjo, Ak., M.Ak., CA; Irta Paramita (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2016)
Abstract : This research was conducted in order to determine and analyze the influence of operational audit the efficiency of the performance of the purchase of PT Envirolab Nusantara, investigate and analyze the influence of operational audit the effectiveness of the performance of the purchase, determine and analyze the effect of operational audits of efficiency and operational audits effectiveness jointly on the performance of purchase PT Envirolab Nusantara. Based on the test results